NANOSPRESSO: toward personalized, locally produced nucleic acid nanomedicines - Estapé Senti, Mariona; Ceccaldi, Alexandre; Luciani, Marta; Saber, Nadine; Schurmann, Paul J. L.; Geerlings, Maurits W.; Holig, Peter; de Beer, Joel; Hannus, Michael; Campbell, Fred; Winter, Martin; van Hoeve, Wim; et al. (Frontiers in Science, 2025)
The NANOSPRESSO project is a pioneering response to the complex challenge of treating orphan diseases, which, despite affecting millions of people globally, have only scant therapeutic options. This initiative represents a paradigm shift by decentralizing the production of personalized nucleic acid nanomedicines. Integrating advanced microfluidic technology with lipid nanoparticle engineering platforms—validated by their efficacy in COVID-19 messenger (m)RNA vaccines—the NANOSPRESSO model enables hospital pharmacists to seamlessly assemble tailored therapeutic cartridges for gene/RNA therapy administration at the patient’s bedside. This innovative model subverts the traditional constraints of high-cost, intricate manufacturing and the instability of nucleic acid-based treatments, offering a streamlined. localized, flexible, and patient-centric alternative. Inspired by the traditional art of compounding in pharmacy, NANOSPRESSO strives to democratize access to innovative treatments for rare diseases, challenging the conventional, monolithic medical approach. Alongside its technological breakthroughs, the project also engages in proactive dialogue with regulatory authorities to ensure compliance with stringent quality, safety, and efficacy standards, applying an array of analytical techniques recently developed for nucleic acid nanomedicines. Orchestrated by an extensive European consortium of multidisciplinary experts, NANOSPRESSO embodies the collaborative spirit driving the next wave of healthcare innovation, placing patients at the center of a precision medicine revolution. This article conveys the core mission of NANOSPRESSO: to redefine the reach and impact of nanomedicine, heralding a future in which personalized therapy for rare and orphan diseases—and potentially other conditions—is a reality, available to patients and affordable by public health systems. We outline the scientific and technological basis for this model, explore various regulatory, legal, economic, and societal implications and challenges, and advocate for interdisciplinary solutions across the research and innovation ecosystem.